Nested-local Wisdom Model for Sustainable Science Education: Enhancing Students’ Conceptual Knowledge and Communication Skills - Andi Asmar; I Gusti Putu Suryadarma; Yuliyanti; Lakilo Laruli (Postgraduate, University of Mataram, 2026)
When science is perceived as disconnected from learners’ social dan cultural contexts, students’ engagement and identity in learning science decline. This study evaluates a nested-local wisdom approach integrating the cultural context of Pinisi boats to enhance students’ conceptual knowledge, communication skills, and concept maps, supporting more meaningful and sustainable science education. This study employed a quasi-experimental design with a non-equivalent control group pretest-posttest involving students from SMPN 32 Bulukumba. Two intact classes (n = 31 each) were selected, and their equivalence was verified using pretest scores and academic records. Data were analyzed using MANOVA dan ANOVA. The results revealed a significant multivariate effect the learning model on all dependent variables (Wilks’ Lambda = 0.212, p < 0.001, ηp² = 0.788), indicating a large effect size. Furthermore, ANOVA results revealed the largest effect size in concept maps (ηp² = 0.682), followed by communication skills (ηp² = 0.642) and conceptual knowledge (ηp² = 0.449). These findings suggest that integrating local wisdom within a nested learning structure supports the development of key science competencies, particularly conceptual knowledge and communication skills, through culturally meaningful learning. Therefore, the nested-local wisdom approach offers a contextually relevant and pedagogically grounded strategy for advancing sustainable science education.